Synergistic effects of crosslinking and chitosan molecular weight on the microstructure, molecular mobility, thermal and sorption properties of porous chitosan/gelatin/hyaluronic acid scaffolds. Issue 18 (24th January 2017) - Acevedo, Cristian A.; Sánchez, Elizabeth; Díaz‐Calderón, Paulo; Blaker, Jonny J.; Enrione, Javier; Quero, Franck
ABSTRACT: In this study, synergistic effects of crosslinking and chitosan molecular weight on the microstructure, molecular mobility, thermal, and sorption properties of porous chitosan/gelatin/hyaluronic acid hybrid foams are reported. Fourier transform infrared spectroscopy has been utilized to confirm the covalent attachment of hyaluronic acid to gelatin and chitosan, and covalent chemical crosslinking between gelatin and chitosan. Detailed image analysis of scanning electron microscopy images of the porous scaffold hydrids reveal that the pore size of the materials formulated using either low‐ or high‐molecular‐weight chitosan increases significantly upon crosslinking using ethyl(dimethylaminopropyl) carbodiimide/N‐Hydroxysuccinimide. These microstructural changes are even more pronounced for the crosslinked hybrid scaffolds formulated using low‐molecular‐weight chitosan, highlighting a synergistic effect between crosslinking and the use of low‐molecular‐weight chitosan. Results obtained using differential scanning calorimetry demonstrate a significant reduction in molecular mobility reduction in molecular mobility for crosslinked scaffolds formed using high‐molecular‐weight chitosan compared to non‐crosslinked hybrids and crosslinked hybrids formulated using low‐molecular‐weight chitosan. Correspondingly, dynamic vapor sorption evidenced significantly lower water vapor sorption for crosslinked scaffolds formulated using high‐molecular‐weight chitosan. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44772. Abstract :